How to Recover Lost Traditions? - Teixeira, E. (Open Schools Journal for Open Science, 2020)
The aim of the project was to engage the community into the recovery and revitalization of some traditional trades and crafts that are at risk of disappearing. At the same time we intended to make students aware of the lost traditions from previous generations that with time are going to be lost. When visiting the place where the black clay of Bisalhães is produced (Intangible Cultural Heritage of Humanity by UNESCO) we realized that there are not enough potters. We went to explore the pottery extraction and production processes and we organized a traditional fair where we exposed all the pottery pieces made by students, so all the community could be aware of Bisalhães pottery. With our enthusiasm we awake the community curiosity for the beauty of traditions.